1994
DOI: 10.1006/bbrc.1994.2902
|View full text |Cite
|
Sign up to set email alerts
|

ROR-γ: The Third Member of ROR/RZR Orphan Receptor Subfamily That Is Highly Expressed in Skeletal Muscle

Abstract: In this study, we describe the identification and cloning of a novel member of the nuclear receptor superfamily. This orphan receptor, referred to as ROR gamma, belongs to the ROR/RZR subfamily. The open reading frame of ROR gamma encodes a protein of 560 amino acid residues with a predicted molecular mass of 63 kD. The amino acid sequence of ROR gamma exhibits a 50 and 51% identity with those of ROR alpha/RZR alpha and RZR beta, respectively, whereas the DNA-binding domains were 89% identical. ROR gamma was l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
188
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(193 citation statements)
references
References 0 publications
4
188
1
Order By: Relevance
“…This contrasts with the more selective expression of RORB and RORC, two other members of the same family (Jetten, 2004). It was reported that RORB is expressed specifically in the brain (Carlberg et al, 1994), and RORC is found at high levels in the skeletal muscle (Hirose et al, 1994). However, we do not have any evidence to rule out the possibility that RORB and RORC also play some role in tumorigenesis in vivo.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…This contrasts with the more selective expression of RORB and RORC, two other members of the same family (Jetten, 2004). It was reported that RORB is expressed specifically in the brain (Carlberg et al, 1994), and RORC is found at high levels in the skeletal muscle (Hirose et al, 1994). However, we do not have any evidence to rule out the possibility that RORB and RORC also play some role in tumorigenesis in vivo.…”
Section: Discussioncontrasting
confidence: 81%
“…It consists of three members: RORA (also named NRF1 by the Nuclear Receptor Nomenclature Committee), RORB (NRF2) (Carlberg et al, 1994) and RORC (NRF3, or TOR) (Hirose et al, 1994). It has been demonstrated that these receptors are critical in the regulation of a number of physiological processes.…”
Section: Introductionmentioning
confidence: 99%
“…The ROR/RZR subfamily of orphan nuclear receptors is a recent addition to the nuclear receptor family and comprises the following members: ROR 1, ROR 2, ROR 3, ROR /RZR and ROR , Giguère et al 1994, Hirose et al 1994. The members of this subfamily bind as monomers preferentially to an AGGTCA core motif preceded by an A/T-rich region (Giguère et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…ROR /RZR is abundantly expressed in the hypothalamus, the pineal gland and the thalamus . ROR is highly expressed in skeletal muscle and may play a role in muscle development (Hirose et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…RORβ knockout mice display a ducklike gait, transient male infertility, abnormal circadian behavior and retinal degeneration [52]. RORγ is found at high levels in skelekal muscle and thymocytes [53,54]. Analysis of RORγ knockout mice revealed significant roles of RORγ in both thymocyte development and lymphoid organogenesis [55].…”
Section: Rors Drug Targets For Cns and Cholesterol-related Diseasesmentioning
confidence: 99%